Alert system of fisherman for secure navigation. Issue 1 (1st May 2022) - Anandh, BA.; Sakthivel, R; Shankar Ganesh, A; Kaviya, A
Abstract: In day-to-day life we hear news about fisherman caught and even kill by naval infantry forces of other country for crossing the international borders. The proposed system can be used by the fisherman to safeguard them with the help of Global Positioning System (GPS) module based alerting system. The system uses the GPS device to get the current location i.e., latitude and longitude values of the boat and is continuously compared with the pre-set values in controller unit. As a result of this, the system alerts by buzzer sound before five hundred meter range and when the boat is near to international borders the speed of the boat is reduced. If the shipper refused to stop the boat and continues further the system alerts the fisheries by voice alarm. At the same time the control unit stops the boat from moving further and the present location is transmitted to the coastguards with the help of RF Transceiver. This is achieved when the boat is before 200 hundred meter range to of the international borders. If the boat tries to cross the international border or the boat is taken over by other countryman naval forces, the location of the boat is transmitted to coastguard port office continuously. This system also has hijack switch and when the switch is pressed it convey the hijack information and the current location to the coastguards continuously.